LB2 PREP, stop & block. (11th August 2022) - Arslan, M; Malik, UF; Srinivasan, K; Conroy, P
Abstract : Background and Aims: To audit on the change of protocol for Peripheral nerve blocks(PNBS) to avoid inadvertent wrong sided block in a tertiary hospital of Dublin. This audit is based on modified version of traditional 'Stop before you block' protocol introduced in 2021. Methods: This audit was based on questionnaires given to each Operation theatre anesthesia room for the nurses and doctors to fill out after PNBS.The duration of audit was of 1 month from 4 th March 2022 to 4 th April 2022..All patients records were reviewed for proper recordings in pre designed structured form. Results: In this duration, total 52 PNBS were done while only 38 forms were filled for audit. .Among these 38 blocks, 30 blocks(78.9%) were forlower limbs, 6(15.7%) for upper limbs and 2 (5.2%) for abdominal procedures. The Prep (preparation)of drugs, equipments and area was done 100% as per hospital policy. However, Stop was done 'verbally' only for 15(39.4%) blocks .But 'mark 'was checked in 36(94.7%) blocks. Finally, Block was given immediately in 37 (97.3%) blocks and it was delayed in 1 (2.6%) block but Prep, stop was not repeated for that block. Conclusions: Conducting an audit on Prep, stop and block protocols is essential for every hospital in which peripheral nerve blocks are done. It avoids the inadvertent wrong sided block which is a 'never event'.The above audit clearly shows room for improvement.